PACIENTE GESTANTE EM TRATAMENTO PARA DEPENDÊNCIA DE CRACK: UM ESTUDO DE CASO - Kolankiewicz, Adriane C. B.; Steidl, Sheila B. d. O.; Rorato, Luciele; Feistel, Eliane C. d. S.; Menin, Gisele E. (Salão do Conhecimento, 2013)
Resumo